Bad Faith and Civil Liability for Unilateral Termination of Cooperation Agreements: A Judicial Analysis of Decision No. 322/Pdt.G/2012/PN.BKS - Alfin Rahman; Dadan Taufik Fathurohman (PT. Caesarindo Triloka Persada, 2026)
The principle of good faith is a fundamental element in contractual relationships, requiring parties to perform agreements fairly and responsibly. However, contractual certainty may be undermined when one party unilaterally terminates an agreement by relying on internal corporate limitations or procedural arguments to avoid contractual obligations. This study examines the legal consequences of bad faith and the civil liability arising from the unilateral termination of a cooperation agreement based on Decision No. 322/Pdt.G/2012/PN.Bks. This study employs normative juridical research using statute, conceptual, and case approaches through the analysis of primary and secondary legal materials. The findings demonstrate that the Defendant’s unilateral termination of the waste management cooperation agreement constituted an unlawful act under Article 1365 of the Indonesian Civil Code because the action was conducted in bad faith, violated contractual fairness, caused actual economic losses, and had a direct causal relationship with the Plaintiff’s loss. The study further reveals that compensation mechanisms for losses arising from unlawful acts may be assessed by applying the principles contained in Articles 1246–1248 of the Civil Code by analogy, covering actual costs, losses, and expected interests. This study contributes to the development of contract law by emphasizing that internal corporate procedural limitations cannot be used as a justification for avoiding contractual responsibility when such actions violate the principle of good faith and cause harm to contractual partners.